Applications of Temperament: A Review of Caregiver-Focused Temperament-Driven Interventions. Issue 1 (2nd January 2018) - Iverson, Sydney L.; Gartstein, Maria A.
ABSTRACT: Research Findings : Temperament, often defined in terms of reactive and regulatory tendencies, has been shown to predict child outcomes over and above other risk factors and represents a critical aspect of social-emotional development. The present article is a systematic review of temperament-based interventions targeting caregivers, wherein the aim is to inform caregivers about temperament in an effort to influence a variety of outcomes, such as goodness of fit, parenting stress, achievement, and behavior problems. In total, 13 randomized and nonrandomized trials were reviewed, with promising outcomes. Temperament-driven interventions have demonstrated the capacity to increase parental knowledge of temperament, reduce behavior problems, improve math and reading achievement, create more positive teacher–child relationships, and reduce numbers of medical visits. Caregivers report satisfaction with and usefulness of the interventions, which suggests promise for future application of temperament-based approaches. Temperament-driven interventions can be leveraged to improve multiple developmental outcomes, especially in early childhood, and are useful for both teachers and parents. Practice or Policy : Implications of temperament-based interventions for early childhood educators are discussed, as are limitations and future directions.